(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. Alle radici del pluralismo della disparità - 3. Le definizioni a contrario - 4. Le minoranze nel sentiero del principio di laicità - 5. Le minoranze religiose alle prese con il genus e la species della laicità - 6. La rilevanza legale delle minoranze religiose - 7. L’autonomia delle confessioni diverse - 8. Le diseconomie esterne del diritto comune delle intese - 9. Come ridurre le diseconomie esterne negative - 10. Conclusioni e prospettive. The Legal Discipline of Minority Religions. The External Diseconomy of Italy’s Favor Religionis ABSTRACT: This article analyses the State’s legal discipline regulating minority religions, which are part of the current religious pluralism in Italy. Pluralism is not new in the Italian context. Various minority religions have long been part of the national scene and often enjoyed a level of public consideration far superior compared to their numerical consistency. However, today in Italy there are religious organizations that, in the light of the traditional ex parte Ecclesiæ favor religionis and the method of state-church(es) relations, stress some difficulties of constitutional relevance. In particular, these difficulties have increasingly come to be seen in terms of “negative externalities”: while creating privileges for the Catholic Church and few minority denominations, it produces unreasonable discriminations against all other religions. That is particularly the case of legal status of “new” minority religious, made up mainly of immigrants.